Study of integrated risk regionalisation method for soil contamination in industrial and mining area. (December 2017) - Guan, Yang; Chu, Chunli; Shao, Chaofeng; Ju, Meiting; Dai, Erfu
Highlights: A method is developed to assess integrated risk in industrial mining areas. Risk regionalization method based on risk, receptors and sources is developed. Innovative application of MMSOILS in Comprehensive human health risk assessment. Abstract: Industrial and mining areas have been included as key governance plots of China's soil management and protection. In this study, we developed an assessment method for soil integrated risk in industrial and mining areas, with a comprehensive consideration of pollution risk, pollution sources and receptors of soil risk. The method consists of four parts, including soil risk assessment, vulnerability assessment of soil risk receptors, risk level assessment of pollution sources and integrated risk assessment. Using this method, we could produce a complete soil risk regionalisation map that presents the total factor risk level of soil contamination of industrial and mining areas in ArcGIS. This study also took a typical industrial and mining area in China as a case and quantitatively and spatially assessed the integrated soil contamination risk. Results showed: (1) the integrated risk of the study area ranged from moderate level to high level; (2) the risk of pollution sources in the study area ranged from moderate level to high level; (3) vulnerability of soil risk receptors in streets was lower than that in the towns.